Synthesis and anticancer properties of 5-(1H-benzoimidazol-2-ylmethylene)-4-oxo-2-thioxothiazolidin-3-ylcarboxilic acids - Volodymyr Horishny; Taras Chaban; Vasyl Matiychuk (Pensoft Publishers, 2021)
The reaction of 1H-benzoimidazole-2-carbaldehyde with 4-oxo-2-thioxothiazolidin-3-ylcarboxilic acids was studied and the combinatorial library of 5-(1H-benzoimidazol-2-ylmethylene)-4-oxo-2-thioxothiazolidin-3-ylcarboxilic acids has been prepared. The structures of target compounds 8a-f, 9 and 10a, b were confirmed by using 1H NMR spectroscopy and elemental analysis. The synthesized compounds were selected by the National Cancer Institute (NCI) Developmental Therapeutic Program for the in vitro cell line screening to investigate their anticancer activity. The tested compounds displayed a weak to medium anticancer activity. The most sensitive cell lines turned out to be SNB-75 of CNS Cancer (GP = 74.84-85.73%) and UO-31, Renal cancer (GP = 71.53-82.16%) and to compound 10a K-562 Leukemia cell lines (GP = 57.14). Graphical abstract